Risk of Radiation Exposure During PCNL - Soufi Majidpour, Heshmatollah (Urology Journal, 2010)
Purpose: Fluoroscopic guidance is a routine practice in endourology; both the physician and the assistances are exposed to some radiation via radiation scatter. Measurement of radiation doses in staff is important, but often these data are not reported. Materials and Methods: We measured radiation exposure during 100 cases of percutaneous nephrolithotomy using lithium fluoride thermoluminescent dosimeters placed at the head, eye glasses, the fingers, and the legs of the operating surgeon, the assistant, and the circulating nurse. Results: The mean screening time was 4.5 minutes (range, 1 to 8 minutes) with mean fluoroscopy tube potential of 73 kVp, and mean tube current of 2.8 mA. The estimated scatter exposure rate at 40 cm from the x-ray beam was 0.47, 0.04, 0.21, and 4.1 ?Gy to the head, eye glasses, the fingers, and the legs of the operating surgeon, respectively. The estimated scatter exposure rate at different points from the x-ray beam was 0.05, 0.01, 0.025, and 0.1 ?Gy to the head, eye glasses, the fingers, and the legs of the assistant, respectively and the estimated scatter exposure rate at all different points from the x-ray beam for circulating nurse was 0 ?Gy. Conclusion: Fluoroscopic screening results in radiation exposure of the medical staff. The surgeon received the maximum radiation exposure, mostly to the legs and very least to the eyes. The assistant received less radiation exposure than the surgeon and the nurse did not receive significant amount of radiation.